A Iniciação Científica Júnior multidisciplinar como facilitadora da alfabetização científica - Rodrigues, Bárbara Daniela Guedes (Universidade Federal de São Carlos, 2016)
This research was conducted by monitoring ten students awarded with high school scholarships (scientific initiation junior multidisciplinary) provided by Circus of Science, an event realized during the Open University directed by professor Pedro Malagutti of Math Department-UFSCar, in 2013. The following process allowed to analyze and observe the scientific literacy of the students facilitated by the scientific initiation junior activities. During 2013 the Circus of Science held a science fair of public school students from São Carlos and awarded the 20 best reports with scholarships from CNPq, a governmental institution. The research started with a small science fair at the public school Archimedes Aristeu Mendes de Carvalho where the first and second years high school students exposed their projects and were selected to present at Circus of Science. After analysis of theirs projects and educational achievement 10 students were selected among 20 that participated and were awarded with the multidisciplinary scholarships. The project comprehended during one year activities in different laboratories, among them Chemistry, Biology, Physics and Mathematic. The researcher monitored these students and applied questionnaires before and after the activities, classes, posters composition and the final projects presented again at the Circus of Science event in 2014. The data were analyzed by scientific literacy point of view based in Miller and Ludke and Andre qualitative methodology.
Scientific Initiation Junior multidisciplinary as facilitator of the scientific literacy
Keywords: Feira de ciência; Alfabetização cientifica; Ensino não formal; Circo da ciência; Science fair; Scientific literacy; Non-formal teaching; Circus of science; CIENCIAS EXATAS E DA TERRA::QUIMICA